Вплив одновісної пружної деформацiї на положення глибоких енергетичних рiвнiв у монокристалах n-Ge<Au> - Федосов, А.; Луньов, С.; Захарчук, Д.; Федосов, С.; Панасюк, Л. (Праці наукового товариства ім. Шевченка, 2011)
The effect of uniaxial elastic deformation X on the change of the location of deep energy level of gold Eс-0,2 eV in n -Ge according to piezo- Hall-effect n = f(X) in a wide area of mechanical tensions X = 0-13•10³ kG /cm² is investigated under a condition X//J//[111]. The change of the energy gap between the deep level Ec-0.2 eV and the lower valleys of a conductivity zone of n Si <Ge> is calculated to be 5,7 ± 0,01•10³ eV per each 10³ kG sm². The state of filling of the energy levels is estimated. The average value of an coefficient was determined at different temperatures.